Digital Transformation and Social Stratification: A Sociological Analysis of Digital Divide in Contemporary Society - Khaeriyah Khaeriyah; Nurasia Natsir (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2025)
The rapid advancement of digital technology has fundamentally transformed social structures, creating new forms of inequality and social stratification. The digital divide has emerged as a critical sociological phenomenon that reflects and reinforces existing social hierarchies while creating new patterns of inclusion and exclusion. This study examines the relationship between digital transformation and social stratification, analyzing how digital access, literacy, and participation contribute to contemporary forms of social inequality. The research investigates the mechanisms through which digital divides reproduce and transform traditional class structures. This sociological inquiry employs a mixed-methods approach, combining quantitative survey data from 500 households across different socioeconomic strata with qualitative ethnographic observations and in-depth interviews with 40 participants. The study utilizes Pierre Bourdieu's theory of capital and Anthony Giddens' structuration theory as analytical frameworks. The findings reveal three distinct digital classes: the "digitally privileged" (25%), "digitally struggling" (45%), and "digitally excluded" (30%). Digital capital significantly correlates with traditional forms of capital (economic, cultural, and social), creating compound advantages for privileged groups. The study demonstrates that digital transformation both reinforces existing inequalities and creates new forms of social differentiation. Digital transformation has become a new dimension of social stratification that intersects with traditional inequality patterns. The digital divide represents not merely a technological gap but a fundamental social divide that requires comprehensive sociological understanding and policy intervention to ensure equitable social development.